2016
DOI: 10.1021/acs.langmuir.6b03325
|View full text |Cite
|
Sign up to set email alerts
|

Two-Component Self-Assemblies: Investigation of a Synergy between Bisurea Stickers

Abstract: ABSTRACT. It is of interest to develop two-component systems for added flexibility in the design of supramolecular polymers, nanofibers or organogels. Bis-ureas are known to selfassemble by hydrogen bonding into long supramolecular objects. We show here that mixing aromatic bis-ureas with slightly different structures can yield surprisingly large synergistic effects. A strong increase in viscosity is observed when a bis-urea with the sterically demanding 2,4,6-trimethylbenzene spacer is combined with a bis-ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…1B). [25][26][27][28][29] BU-moieties allow for more efficient surface functionalization compared to UPy-units, resulting in a more pronounced cellular response. 29 In combination with the aforementioned features, the intrinsic modular nature of supramolecular BU-moieties makes them eminently suitable for the creation of complex screening libraries.…”
Section: Introductionmentioning
confidence: 99%
“…1B). [25][26][27][28][29] BU-moieties allow for more efficient surface functionalization compared to UPy-units, resulting in a more pronounced cellular response. 29 In combination with the aforementioned features, the intrinsic modular nature of supramolecular BU-moieties makes them eminently suitable for the creation of complex screening libraries.…”
Section: Introductionmentioning
confidence: 99%
“…Biosci. 2019, 20,1900277 processing, hence similar properties between PCL-BU membranes and PCL-BU with PEG blended membranes. [32,40,41] Hydrophobicity measurements and cell adhesive results suggested that the bottom is enriched with PEG.…”
mentioning
confidence: 78%
“…Supramolecular bis‐urea (BU) motifs have been successfully employed to achieve intimate mixing of components 19–21. The motifs are proposed to assemble through bifurcated hydrogen bonding into ribbon‐like structures, three to six ribbons are proposed to assemble into nanoscale fibers 22–26.…”
Section: Membrane Properties Of Different Supramolecular Polymer Blendsmentioning
confidence: 99%
See 2 more Smart Citations